Enhancing Transparency and Comprehensiveness of Scholarly Articles by the Use of Reporting Guidelines - Sharma, Apurb; Aryal, Marisha (Nepalese Heart Journal, 2024)
Biomedical research is an ever evolving field. The integrity and impact of research work depends heavily upon transparent reporting. It is crucial for Nepalese Heart Journal to emphasize the significance of adhering to robust reporting guidelines. These guidelines are not just a checklist of items like requisites but now they are the foundation of scientific publications that assure clarity, reproducibility, and credibility.